STUDI ETNOBOTANI TUMBUHAN OBAT PADA SUKU SEKO DI DESA TANAH HARAPAN, KABUPATEN SIGI, SULAWESI TENGAH - Apriyanto S. Tapundu; Syariful Anam; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2015)
Aresearch entitled “Ethnobotanical Study of Medicinal Plant in the Seko ethnic group in Tanah Harapan Village, Sigi Regency, District Central Sulawesi” has been carried out from March to April 2015. The research objective was to obtain the information of Plants diversity and its part that utilized as traditional medicine. The research was done by two methods that is using semi structure interview technique to 40 respondents with quisioner sheet and direct interview to village Shaman. The result showed that there were (55) plants species that used by the Seko ethnic group in Tanah Harapan Village. The highest percentase that used in the part of plants were 43% of leaves and the level of community knowledge for using the plant as a traditional medicine a much as 97,5%. The type of the illness that can be threated are chronic, infections, non-infections and also to health care.Keywords: Seko Ethnic, Tanah Harapan Village, Sigi Central Sulawesi, Ethnobotanical Medicinal Plant